Hinged Carboxylate in the Artificial Distal Pocket of an Iron Porphyrin Enhances CO2 Electroreduction at Low Overpotential - Adrien Smith; Philipp Gotico; Régis Guillot; Stéphane Le Gac; Winfried Leibl; Ally Aukauloo; Bernard Boitrel; Marie Sircoglou; Zakaria Halime (Advanced Science)
Abstract To efficiently capture, activate, and transform small molecules, metalloenzymes have evolved to integrate a well‐organized pocket around the active metal center. Within this cavity, second coordination sphere functionalities are precisely positioned to optimize the rate, selectivity, and energy cost of catalytic reactions. Inspired by this strategy, an artificial distal pocket defined by a preorganized 3D strap is introduced on an iron‐porphyrin catalyst (sc‐Fe) for the CO2‐to‐CO electrocatalytic reduction. Combined electrochemical, kinetic, and computational studies demonstrate that the adequate positioning of a carboxylate/carboxylic group acting in synergy with a trapped water molecule within this distal pocket remarkably enhances the reaction turnover frequency (TOF) by four orders of magnitude compared to the perfluorinated iron‐tetraphenylporphyrin catalyst (F20Fe) operating at a similar low overpotential. A proton‐coupled electron transfer (PCET) is found to be the key process responsible for the unexpected protonation of the coordinating carboxylate, which, upon CO2 insertion, shifts from the first to the second coordination sphere to play a possible secondary role as a proton relay.